Multi-Instrument Observation of the Ionospheric Irregularities and Disturbances during the 23–24 March 2023 Geomagnetic Storm - Tahir, Afnan; Wu, Falin; Shah, Munawar; Amory-Mazaudier, Christine; Jamjareegulgarn, Punyawi; Verhulst, Tobias G.W.; Ameen, Muhammad Ayyaz (My University, 2024)
This work investigates the ionospheric response to the March 2023 geomagnetic storm over American and Asian sectors from total electron content (TEC), rate of TEC index, ionospheric heights, Swarm plasma density, radio occultation profiles of Formosat-7/Cosmic-2 (F7/C2), Fabry-Perot interferometer driven neutral winds, and E region electric field. During the storm’s main phase, post-sunset equatorial plasma bubbles (EPBs) extend to higher latitudes in the western American longitudes, showing significant longitudinal differences in the American sector. Over the Indian longitudes, suppression of post-sunset irregularities is observed, attributed to the westward prompt penetration electric field (PPEF). At the early recovery phase, the presence of post-midnight/near-sunrise EPBs till post-sunrise hours in the American sector is associated with the disturbance of dynamo-electric fields (DDEF). Additionally, a strong consistency between F7/C2 derived amplitude scintillation (S4) ≥ 0.5 and EPB occurrences is observed. Furthermore, a strong eastward electric field induced an increase in daytime TEC beyond the equatorial ionization anomaly crest in the American region, which occurred during the storm’s main phase. Both the Asian and American sectors exhibit negative ionospheric storms and inhibition of ionospheric irregularities at the recovery phase, which is dominated by the disturbance dynamo effect due to equatorward neutral winds. A slight increase in TEC in the Asian sector during the recovery phase could be explained by the combined effect of DDEF and thermospheric composition change. Overall, storm-time ionospheric variations are controlled by the combined effects of PPEF and DDEF. This study may further contribute to understanding the ionospheric responses under the influence of storm-phase and LT-dependent electric fields.
Keywords: DDEF; disturbed neutral winds; equatorial plasma bubbles; geomagnetic storm; ionospheric disturbances; ionospheric irregularities; PPEF